Animal-assisted therapy and occupational therapy. Issue 1 (2nd January 2017) - Andreasen, Gena; Stella, Tiffany; Wilkison, Megan; Szczech Moser, Christy; Hoelzel, Allison; Hendricks, Laura
ABSTRACT: The use of animals for therapeutic purposes has been documented in the literature for centuries. This review will highlight evidence of the benefits of animal-assisted therapy as well as provide a plethora of resources for therapists interested in learning more about how animals can provide restorative benefits for their clients.